Study, design and manufacture eddy current probes for industry applications - Nguyen, Phuc; Nguyen , Van Thuy; Vuong , Binh Duong; Do , Minh Duc; Trinh , Dinh Truong; Do , Tung Khanh; Dang, Quang Trung (Nuclear Science and Technology, 2016)
This study is based on the studying, designing and manufacturing of eddy current probes for industry applications. The main tasks of this study include: + Describes the overview and classification of eddy current probes (which can be classified into three categories based on the mode of operation: absolute eddy current probe, differential eddy current probe and reflect eddy current probe). + Describes the three methods of probe designing and manufacturing (including experimental, analytical and numerical designs). + Describes the designing and manufacturing of eddy current probes for industry applications, which based on experimental and analytical methods. Based on this study, we have successfully manufactured some current probes (including absolute eddy current probe, differential eddy current probe and reflect eddy current probe) for surface and tube inspections.